Mr. Smith and the Preachers: The Economics of Religion in the Wealth of Nations - Anderson, Gary M. (Journal of Political Economy, 1988)
The extension of economic analysis to problems beyond the domain of formal markets and explicit prices represents a major recent intellectual development. But "economic imperialism" is not new and was not invented in Chicago. Adam Smith, in his Wealth of Nations, extended economic reasoning to a variety of nonmarket exchange problems. One example is his analysis of religious behavior. Smith viewed participation in religion as a rational device by which individual enhanced the value of their human capital. He also explained the behavior of the clergy and other suppliers of religious services from an economic perspective.